The Influence of Organizational Culture and Employee Engagement on Employee Performance With Organizational Commitment as a Moderation Variable at the BPJS Ketenagakerjaan Medan Kota Branch Office and Sumbagut Regional Office - Drixen Alexander Mawuntu; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
This study was conducted to find out the Influence of Organizational Culture and Employee Engagement on Employee Performance with Organizational Commitment as a Moderating Variable at the BPJS Employment Medan Kota Branch Office and the Sumbagut Regional Office. Organizations, both companies and government agencies in carrying out their activities, of course, need human resources that support efforts to achieve the goals that have been set by the organization, the success of an agency / organization is not only determined by the facilities owned, but also the availability of reliable human resources. The results of this study are as follows: Organizational Culture has a positive and significant effect on Employee Performance with the original sample value of 0.226 and p values of 0.015. Employee Engagement had a positive and significant effect on Employee Performance with the original sample value of 0.025. Organizational Commitment has a positive and significant effect on Employee Performance with the original sample value of 0.457 and p values of 0.003. Organizational Culture affects Employee Performance moderated by Organizational Commitment with an original sample value of -0.218 and p values of 0.045. Employee Engagement has an effect on Employee Performance moderated by Organizational Commitment with an original sample value of 0.098 and p values of 0.228.